Covid-19 Self Isolation Management, East Sumba District - O.BT Liunokas; Oktofianus Sila; Tri Maryati (Green Publisher Indonesia, 2022)
The status of a global pandemic or epidemic indicates that the spread of COVID-19 is very fast and worrying, namely Covid 19 1166 cases were recorded as of April 30, 2021, 802 cases were declared cured and 328 were treated and 36 people were declared dead. With details of cases of self-isolation at home 269 people, 32 cases treated at the Cendana Hotel and 27 cases treated at the Umbu Rara Meha Hospital, Waingapu. The purpose of the study was to conduct a field analysis in the application of management functions in Isoman (Independent Isolation) of Covid-19 patients in East Sumba Regency and to analyze the management needs of Covid-19 patient care in performing self-isolation at home. This research method is a survey study of descriptive data analyzed in a frequency table, namely the importance of implementing the management functions of coordination, control/supervision, budgeting/financing and evaluation of patients during COVID-19 self-isolation. The number of samples targeted was accidental sampling, namely samples that happened to be present during the study take place. Conclusion: East Sumba COVID-19 self-isolation patients with coordination management were 46% no coordination, 29% patients were not monitored, 37% did not receive fees and 34% were not evaluated.